Research Trends in Islamic Studies on Journal of Research and Development and Training Center Ministry of Religious Affairs: Using Co-Words - Hariyah, Hariyah (Record and Library Journal, 2016)
Since published in 1976, no studies about the development of the theme or subject of the journal articlesÂ  published by Research and Development and Training Center Ministry of Religious Affairs, that are useful to see the development of science onÂ  religious social fields. Based on that, the aim of this paper is to find out research trends in Islamic studies on journal articles published by Research and Development and Training Center Ministry of Religious Affairs in 2005 â 2014. This study uses analysis of co-words with exploratory quantitative approach. This approach explores areas that have not been studied previously. The whole issue of the journal article Research and Development and Training Agency Ministry of Religious Affairs, published in 2005 - 2014 are used as the unit of analysis in this study. The article studied consisted of 1,107 articles contained in four journals. The results showedÂ Subject (descriptor) most appear on clustering over a span of 10 years (2005-2014) are the Islamic Education and Concord. This suggests that the study of Islamic Education and Concord almost throughout the year. Besides, this subject in accordance with the mission of Ministry of Religious Affairs and strategic plan of Research and Development and Training Agency. The distribution of other subjects such as Islamic Manuscripts, Religion, InterReligious Forum, Pornography, Jihad, Islamic Sects, Civil Society, Quran, Conflict, Muslim Scholar, Zakat are popular subjects that became a topic of research over a span of ten years. This subject does not always show up every year and the number of articles are smaller.Â